The Effects of Service Quality, Competitive Prices and Product Quality on Customer Satisfaction - FEBRYANTO, FEBRYANTO; BERNARTO, Innocentius (Journal of Environmental Management and Tourism, 2019)
As time goes by, restaurant businesses increase significantly in such a way that they encourage businessmen to be aware of improving the competitive advantages to compete tightly. The purpose of this study is to determine whether service quality, competitive prices, and product quality have positive and significant influences on customer satisfaction in the KYF Restaurant, Tangerang, Indonesia. In this study, the data were collected by using the questionnaires. The method used in this study was the survey method. The population in this study refered to the customers of the KYF Restaurant. The samples in this study consisted of 100 respondents and convenience sampling was chosen. The statistical analysis that was used in this study was the PLS-SEM (Partial Least Square-Structural Equation Modeling) with the assistance of the SmartPLS 3.2.6 software. The research results have shown that service quality, prices, and product quality indicate positive and significant influences on customer satisfaction in the KYF Restaurant.